(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
The process of measuring the change in the diameter of the pupil is called pupillometry. The pupil dilates and constricts quickly as a response to either change in the brightness of the visual field or a change in cognitive workload. Task induced dilation of pupils under controlled conditions such as light intensity, the posture of the body, emotional status, and arousal is called the task-evoked pupillary response (TEPR). The measurement of pupillary movements may be used to reliably and involuntarily index the extent of central processing allocated to a particular cognitive task. The objective of the present study is to find if Pupillometry can tap change in cognitive load and play a role in determining and assessing language processing, using music as stimuli. 20 adult undergraduate regular University students participated in this study; the population was primarily Hindi speaking. Peak dilation (PD) of both the Right and Left eyes was measured using a Pupillometer. Measurement was taken under the 1) standard clinical condition (baseline) and other conditions with earphones on; 2) instrumental music, 3) regular Bollywood Hindi rap music and 4) foreign music were played (experimental condition). Analysis was done across various conditions, using SPSS. T-test analysis was also done. Peak dilation across typical conditions and with three cognitive load conditions (music) was calculated. A significant difference across the conditions (p<0.05) was obtained in this study. The observation concluded that with an increase in cognitive load via music, the peak dilation of the pupillary diameter increased. Unique pupillary response of each individual across various cognitive task makes it